2018
DOI: 10.1186/s12885-018-4344-3
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid sensitizes metformin-resistant human renal cell carcinoma cells by upregulating H3 acetylation and EMT reversal

Abstract: BackgroundMetformin (Met) is a widely available diabetic drug and shows suppressed effects on renal cell carcinoma (RCC) metabolism and proliferation. Laboratory studies in RCC suggested that metformin has remarkable antitumor activities and seems to be a potential antitumor drug. But the facts that metformin may be not effective in reducing the risk of RCC in cancer clinical trials made it difficult to determine the benefits of metformin in RCC prevention and treatment. The mechanisms underlying the different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 55 publications
1
16
1
Order By: Relevance
“…These data are coherent with previous reports that show beneficial effects of HDACi against RCC cells and EMT (Chun 2018;Jones et al 2009a, b;Juengel et al 2014;Mao et al 2017). Furthermore, HDACi counteracted the acquired resistance of RCC cells against the mammalian target of rapamycin-inhibitor everolimus and the glucose-regulating biguanide metformin (Juengel et al 2014;Wei et al 2018). In light of the chemoresistance and the poor prognosis of metastatic RCC (Barbieri et al 2017;Chang et al 2019), these findings suggest that HDACi pose an interesting therapeutic option for this cancer type.…”
Section: Figmentioning
confidence: 94%
“…These data are coherent with previous reports that show beneficial effects of HDACi against RCC cells and EMT (Chun 2018;Jones et al 2009a, b;Juengel et al 2014;Mao et al 2017). Furthermore, HDACi counteracted the acquired resistance of RCC cells against the mammalian target of rapamycin-inhibitor everolimus and the glucose-regulating biguanide metformin (Juengel et al 2014;Wei et al 2018). In light of the chemoresistance and the poor prognosis of metastatic RCC (Barbieri et al 2017;Chang et al 2019), these findings suggest that HDACi pose an interesting therapeutic option for this cancer type.…”
Section: Figmentioning
confidence: 94%
“…Studies have shown that the degree of histone acetylation in renal cell carcinoma is low . The acetylation of histone H3 is diminished in the RCC 786-M-R cells (Wei et al 2018). The histone H3 in BNIP3 (bcl-2/adenovirus E1B 19 kDa interacting protein 3) promoter of both 786-O and ACHN is deacetylated, while the histone H3 in BNIP3 promoter of A498 is acetylated .…”
Section: Discussionmentioning
confidence: 97%
“…Heparin can bind to fibroblast growth factors (FGFs) and modulate their signaling pathways (34). VA is a histone deacetylase inhibitor that can up-regulate H3 acetylation and repress EMT (28). Although sumarin is well known for its antiviral and antiparasite effects (35), it was shown to inhibit mesodermal induction and formation in early Xenopus and sea urchin embryos (29,36).…”
Section: Discussionmentioning
confidence: 99%
“…As differentiated EEC-iPSCs had higher expression of immune response genes and a higher correlation with HSMM, we reasoned that these differentiated EEC-iPSCs exhibited an enhanced mesodermal identity, as both the immune system and skeletal muscles derive from the mesoderm. To directly assess whether the mesodermal activation is associated with the commitment defects of EEC-iPSCs and whether repressing mesodermal activation can enhance epidermal differentiation of EEC-iPSCs, we tested 3 inhibitors that can repress mesodermal induction, heparin, valproic acid (VA), and suramin (27)(28)(29).…”
Section: Epidermal Differentiation Enhanced By Inhibitors Of Mesodermalmentioning
confidence: 99%